Characterization of luminescent ITO:Tb and AZO:Tb thin films prepared by radio frequency magnetron sputtering - Llontop López-Dávalos, Paul David (Pontificia Universidad Católica del Perú, 2023)
This thesis investigates the effects of introducing terbium to indium tin oxide (ITO) and aluminum zinc oxide (AZO) thin films on their electrical, optical and light emission properties. The films were prepared by radio frequency magnetron co-sputtering with active cooling during deposition. The samples maintained a high optical transmittance in the ultraviolet and visible spectral regions. ITO:Tb showed a low electrical resistivity ranging from 5×10−3 Ω·cm to 0.3Ω·cm, whilst AZO:Tb resulted with a high resistivity which could not be measured with the available equipment. Tb-related luminescence was obtained in ITO:Tb after annealing at 470 ◦C in air at atmospheric conditions. Contrastingly, AZO:Tb showed characteristic Tb luminescence in the as-grown state and further annealing treatments reduced the Tb-related intensity. For both materials, the optical transmittance was measured at each annealing temperature to track the changes in the optical parameters such as optical band gap and Urbach energy. Additionally, exciton binding energy in the case of AZO:Tb was also registered. Together with cathodoluminescence and photoluminescence (PL) measurements, the compromise between the achieved light emission intensity, optical and electrical properties was assessed for each material. Temperature dependence of the Tb-related luminescence and thermal quenching was assessed by temperature-dependent PL measurements from 83K to 533K under non-resonant indirect excitation. Thermal quenching activation energies suggest an effective energy transfer mechanism from the host to the Tb ions. In the case of ITO:Tb, it is assumed that a short-range charge trapping process and subsquent formation of bound excitons to Tb ion clusters is occuring at low sample temperatures. This indirect excitation mechanism is modeled using a spherical potential-well and a tight-binding one-band approximation models. For AZO:Tb, a similar approach is carried out, although the excitons are assumed to be bound to Tb ion clusters or Tb complexes that arise from the coordination with AZO intrinsic defects.
Keywords: Películas delgadas; Aluminio; Radiofrecuencia; https://purl.org/pe-repo/ocde/ford#1.03.00